Patient characteristics, interventions and outcomes of 1151 rapid response team activations in a tertiary hospital: a prospective study. Issue 12 (December 2016) - White, K.; Scott, I. A.; Bernard, A.; McCulloch, K.; Vaux, A.; Joyce, C.; Sullivan, C. M.
Abstract : Background: The characteristics of mature contemporary rapid response systems are unclear. Aim: To determine the patient characteristics, processes and outcomes, both in‐hospital and post‐discharge, of a well‐established rapid response system in a tertiary adult hospital. Methods: This is a prospective study of consecutive rapid response team (RRT) activations between 1 July and 25 November 2015. Variables included patient characteristics, timing, location and triggers of RRT activations, interventions undertaken, mortality and readmission status at 28 days post‐discharge. Results: A total of 1151 RRT activations was analysed (69.1 per 1000 admissions), involving 800 patients, of whom 81.5% were emergency admissions. A total of 351 (30.5%) activations comprised repeat activations for the same patient. Most activations (723; 62.8%) occurred out of hours, and 495 (43%) occurred within 48 h of admission. Hypotension, decreased level of consciousness and oxygen desaturation were the most common triggers. Advanced life support was undertaken in less than 7%; 198 (17.2%) responses led to transfer to higher‐level care units. Acute resuscitation plans were noted for only 29.1% of RRT activations, with 80.3% stipulating supportive care only. A total of 103 (12.6%) patients died in hospital, equalling 14 deaths per 100 RRT activations. At 28 days, 150 (18.8%) patients had died, significantly more among those with multiple versus single RRT activations (24.9 vs 16.6%; odds ratio 1.66, 95% confidence interval 1.31–2.44; P = 0.013). Conclusion: Relatively few RRT activations are associated with acute resuscitation plans, and most interventions during RRT responses are low level. The high rate of post‐RRT deaths and transfers to higher‐level care units calls for the prospective identification of such patients in targeting appropriate care.